A transformation of respondently conditioned stimulus function in accordance with arbitrarily applicable relations. - Roche, B (1997)
Adult male subjects saw a sexual film clip paired with a nonsense syllable (C1). Similarly, an emotionally neutral film clip was paired with a second nonsense syllable (C3). Responses to the nonsense syllables were recorded as skin resistance responses. Subjects were also trained in a series of related conditional discriminations, using the C1 and C3 stimuli, from which the following equivalence relations were predicted; A1-B1-C1, A2-B2-C2, and A3-B3-C3. Some subjects were given matching-to-sample (equivalence) tests after the conditional discrimination training (Experiment 1), whereas others were not (Experiment 2). Subjects were tested for a transformation of eliciting functions by presenting the A1 and A3 stimuli, which were related through equivalence to C1 and C3, respectively. Five of the 6 subjects who showed significantly greater conditioned responses to C1 than to C3, also showed significantly greater skin resistance responses to A1 than to A3. Two additional subjects demonstrated a transformation of an eliciting stimulus function in accordance with five-member equivalence relations (Experiment 3), and another 5 subjects demonstrated similar effects in accordance with the relations of sameness and opposition (Experiment 4).